Visible light communication with smartphone (iPhone) - Tan, Cherry Wanyi (2017)
As of current, the latest Light Emitting Diode (LED) technology opens up a wide area for new applications, new technical possibilities at a reduced cost. Conventional lighting infrastructure such as the fluorescent light bulbs are being replaced by LED lights.